Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw Terhadap Sikap Tanggung Jawab Siswa Dalam Pembelajaran Agama Islam (Studi Di SMA Ciledug Al-Musaddadiyah Garut Kelas XI) - Maria, Anly; Nurfadilah, Ekky (STAI Al-Musaddadiyah Garut, 2023)
Responsibility is defined as an individual's willingness to bear the consequences of their decisions regarding choices made, accepted with full willingness, awareness, and commitment. Currently, the level of responsibility among students in Islamic religious education is lacking, with many students not fully recognizing their responsibilities, particularly in their studies. The Jigsaw cooperative learning model, which emphasizes collaboration and mutual dependence among students, has the potential to enhance their sense of responsibility. This study aims to describe: (1) the profile of student responsibility in Islamic religious education in grade XI at SMA Ciledug before the intervention, (2) the application of the Jigsaw cooperative learning model in Islamic religious education in grade XI at SMA Ciledug, and (3) the impact of the Jigsaw cooperative learning model on the sense of responsibility among students in grade XI at SMA Ciledug after the intervention. The research employed a pre-experimental method with a One-Group Pretest-Posttest design. Data collection techniques included observation, questionnaires distributed to 17 respondents, and document studies. Data analysis was conducted using statistical methods. The results, based on statistical analysis, indicate that the calculated t-value is greater than the t-table value (t_calculated > t_table), with a t-value of -6.696 or 6.696 > t-table value of 1.745. Therefore, it can be concluded that the Jigsaw cooperative learning model has a significant impact on enhancing students' sense of responsibility in Islamic religious education in grade XI at SMA Al-Musaddadiyah Garut. Keywords: Jigsaw Cooperative Learning Model, Student Responsibility, Islamic Religious Education